PENINGKATAN PARTISIPASI MASYARAKAT DALAM PENGELOLAAN POTENSI DESA BERBASIS IPTEK DI DESA BALUK - I.K. A. Atmika; I.G.A.K. Suriadi; I.D.G.A. Subagia (Buletin Udayana Mengabdi, 2018)
The themes of the KKN-PPM program in Baluk village are: Empowerment and Improvement ofcommunity participation in the management of the potential of science and technology-basedvillages to Mandiri villages through programs such as: public health programs: householdsanitation counseling and counseling of clean and healthy lifestyle in children. school children.Environmental program: reforestation activities in the area along the village road. Increasedproductivity of community / business groups in the production of soy milk through the introductionand application of blender machine technology. Cost-efficiency with the introduction and application of biogas / biogas portable biogas technology with the use of cow dung for a day-to-dayenergy source. Increased public participation in all KKN-PPM activities. Increased communityself-reliance in continuing every program that has been accompanied during KKN-PPM activities.Method of implementation of activities is divided into three stages. The first stage is preparationand briefing, second phase of implementation of activities in the field, and third stage evaluationand monitoring for correction and refinement of program sustainability. Preparatory phase beginswith field supervisors and students with the village apparatus and community leaders to determinethe priority scale of activities based on the conditions and potentials that exist in the community,this activity was held on July 20, 2017. The implementation of activities carried out withcounseling and practice in the field , as well as mentoring by students participating KKN during thefield. The dedication activity is held for one month starting from July 22, 2017 until August 27,2017. While the third stage is the evaluation and monitoring conducted by the team of fieldsupervisors and coordinators of KKN to see the impact and sustainability of programs that havebeen implemented.